KARAKTERISTIK KUALITATIF SAPI KRUI DI KABUPATEN PESISIR BARAT LAMPUNG - Ningsih, St Fitria; Sulastri, Sulastri; Hamdani, M. Dima Iqbal (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
This research was conducted in April, 2017 at South Pesisir subdistrict, West Pesisir Regency, Lampung Province to study qualitative characteristic of Krui cattle. Sixty tails male cattle and 60 tails female cattle about 2 years old were observed in this research. Sample observed were decided by purpossive sampling method. Variables observed were head’s color, body’s color, face’s shape, horn’s shape, presence or absence of wattle and hump. Data resulted in this research anlaysed by descriptive. Result of this research in observation of colour of head indicated that most of male cattle (18,33%) dan female cattle (21,67%) was brown. Result of observation in colour of body, most of male cattle (23,33%) was brown and female cattle (26,67%) was brown and white. Shape of head of male cattle (75%) and female cattle (71,67%) were triangle and slim. No hump in the most of male cattle (66,67%) and female cattle (75%). Most of male cattle (81,67%) and female cattle (85%) have wattle. Most of male cattle (70%) and female cattle (76,67%) have horn silak congklang type. Colour of tail in male amd female cattle sere fit with the colour of body and the colour of tip of tail wer black. It could be concluded that Krui cattle were same eith Bali cattle ans Pesisir cattle. The color of body and head Krui cattle was brown, The shape of head was triangle.Have wattle. Little hump. The shape horn was silak congklong. Colour of tail in male amd female cattle sere fit with the colour of body and the colour of tip of tail wer black. Key words: Krui cattle, head’s color, body’s color, face’s shape, horn’s shape, wattle and the shoulder